2014
DOI: 10.3389/fncir.2014.00083
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory projections from the ventral nucleus of the trapezoid body to the medial nucleus of the trapezoid body in the mouse

Abstract: Neurons in the medial nucleus of the trapezoid body (MNTB) receive prominent excitatory input through the calyx of Held, a giant synapse that produces large and fast excitatory currents. MNTB neurons also receive inhibitory glycinergic inputs that are also large and fast, and match the calyceal excitation in terms of synaptic strength. GABAergic inputs provide additional inhibition to MNTB neurons. Inhibitory inputs to MNTB modify spiking of MNTB neurons both in-vitro and in-vivo, underscoring their importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 54 publications
1
61
0
Order By: Relevance
“…The excitatory input to MNTB originates from globular bushy cells in the contralateral ventral cochlear nucleus (Held 1892(Held , 1893Tolbert et al 1982). One major source of inhibitory inputs to MNTB is the ipsilateral VNTB (Albrecht et al 2014;Thompson and Schofield 2000), which in turn receives excitatory input from globular bushy and/or stellate cells in the contralateral cochlear nucleus Thompson 1998;Warr 1969). Thus both inputs to MNTB originate, directly or indirectly, in the contralateral cochlear nucleus, are of auditory nature, respond to sound stimulation with ongoing firing patterns, have relatively high activity levels, and are very likely characterized by spontaneous activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The excitatory input to MNTB originates from globular bushy cells in the contralateral ventral cochlear nucleus (Held 1892(Held , 1893Tolbert et al 1982). One major source of inhibitory inputs to MNTB is the ipsilateral VNTB (Albrecht et al 2014;Thompson and Schofield 2000), which in turn receives excitatory input from globular bushy and/or stellate cells in the contralateral cochlear nucleus Thompson 1998;Warr 1969). Thus both inputs to MNTB originate, directly or indirectly, in the contralateral cochlear nucleus, are of auditory nature, respond to sound stimulation with ongoing firing patterns, have relatively high activity levels, and are very likely characterized by spontaneous activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggested that the main source of inhibition to MNTB may originate from the VNTB (Albrecht et al 2014). VNTB neurons, like the majority of auditory brain stem neurons, receive inputs that are highly active during the presentation of sound and additionally are spontaneously active during acoustic silence.…”
Section: Characterization Of Ipscs Under In Vivo-like Activity Levelsmentioning
confidence: 99%
See 3 more Smart Citations